Cinsel sağlık eğitiminin önemi - (:unkn) unknown (My University, 2010)
Cinsel sağlık eğitimi doğumla başlayan ve tüm yasam boyu devam eden bir süreçtir. Cinsel sağlık eğitiminin temel amacı cinsel sağlığı korumaktır. Cinsel sağlığın korunması, geliştirilmesi ve sürdürülmesi bireylerin cinsellik ve cinsel sağlık konusunda bilinçlenmelerine bağlıdır. Bilinçlenme ailede başlar, okul öncesi, okul ve okul sonrası gibi yaşamın her döneminde gereksinime uygun geniş kapsamlı cinsel sağlık eğitimiyle sağlanır. Dünyanın birçok ülkesinde özellikle gelişmekte olan ülkelerde olduğu, gibi Türkiye'de de-sistemli bir cinsel sağlık eğitimi bulunmamaktadır. Bunun temelinde cinsel sağlık eğitiminin gençleri cinsel İlişkiye teşvik edeceği kanısı olduğu düşünülmektedir. *Oysa araştırmalar kapsamlı bir cinsel eğitimin; cinsel iilişkiyi ertelediği, cinsel ilişki sıklığını azalttığı, gençlerin cinsel yolla bulaşan hastalıklardan daha iyi korunduğu ve daha olumlu arkadaşlık ilişkileri kurduğunu göstermektedir. Ayrıca bu eğitimin bireyin fiziksel, duygusal ve cinsel gelişimini anlamasına, güvenli ve sağlıklı cinsel davranış geliştirmesine yardımcı olmakla birlikte başkalarının görüşlerine, davranışlarına ve yaşam şekillerine, saygılı olma bilinci kazandırdığı bilinmektedir.

Sexual health education is a process starting with birth and continuing throughout the life of the individual. The main aim of sexual health education is to protect and maintain sexual health. The protection, development and sustainability of the sexual health, depend on the individuals becoming conscious about sex and sexual health. Consciousness begins within the family, in every period of life like pre-school, school and after school, it is gained by a comprehensive sexual health education appropriate to the necessity. İn most other countries in the world especially in the developing ones a systematic sexual health education does not exist in Turkey. The main reason for this is that sexual education is thought to encourage adolescents ta have early sexual experience. However, research on this subject indicates that comprehensive sexual health education delays sexual intercourse, decreases sexyal intercourse frequency, protects teenagers against sexually-transmitted diseases and helps them to have beter relationshipswith other. Besides this, it is known that sexual health enables individuals to comprehend their own psysical, emotional and sexual developments, helps them to develop safe and healthy sexual behaviours, as well aa teaching them to respect the behaviours and lifestyles of other people.
The importance of sexual health education
Keywords: Tıbbi İnformatik; Davranış Bilimleri; Eğitim, Eğitim Araştırmaları; Aile Çalışmaları